Overview Pandemi Covid-19 di Kabupaten Bolaang Mongondow - Debri Rizki Faisal; Ni Wayan Deisy Arisanti (Jurnal Kesehatan Masyarakat, 2022)
The first Covid-19 case in Indonesia was found on March 2, 2020. In a short time, Covid-19 cases have spread to various provinces in Indonesia. The purpose of the study was to look at the description of the Covid-19 pandemic in Bolaang Mangondow Regency in 2020-2021. This study uses Covid-19 surveillance data from the Bolaang Mangondow District Health Office for 2020-2021. The data were analyzed descriptively by presenting the daily trend of cases, percentage and frequency of cases based on gender, age group and vaccine status. Data is presented in the form of graphs and tables. The first Covid-19 case in Bolaang Mangondow Regency was released on May 20, 2020. The 2nd to 4th cases came from travellers who were import cases. Covid-19 cases continue increased where in 2020 the total cases were 147 cases and by the end of 2021 the total cases were 842 cases. The 2020-2021 period saw several waves due to high community mobility, active early detection in the field and massive transmission of the Delta variant. Distribution based on sub-districts showed that Lolak had 130 cases (4.35 cases per 1000 population), Central Dumoga 119 cases and East Dumoga 114 cases. The total who died during the 2 years of the pandemic was 45 people (CFR 5.34%). The increase in cases is due to the community's high mobility which causes uncontrolled transmission. Measures for control of the pandemic with active epidemiological surveillance, vaccination programs, and most importantly the implementation of health protocols by the community.